Lactic Acid Bacteria as a Live Delivery System for the in situ Production of Nanobodies in the Human Gastrointestinal Tract - del Rio, Beatriz; Redruello, Begoña; Fernandez, Maria; Martin, M. Cruz; Ladero, Victor; Alvarez, Miguel A. (Frontiers in Microbiology, 2019)
Lactic acid bacteria (LAB) are among the most widely used microorganisms in food fermentation. However, some LAB species can also be used as live vehicles for the in situ delivery of therapeutic molecules to the mucosa of the human gastrointestinal tract (GIT). Many LAB species have 'qualified presumption of safety' status, and survive passage through the GIT. Indeed, some are part of the usual GIT microbiota. These are appropriate candidates for the in situ production of recombinant prophylactic and therapeutic proteins. Live recombinant LAB that produce microbial antigens have been shown to elicit an immune response that confers protection against the corresponding pathogens; these LAB could therefore be used as oral vaccines. In addition, some LAB have been genetically engineered to produce therapeutic, neutralizing antibodies. The variable domain of heavy-chain-only antibodies from camelids - known as VHH antibodies or nanobodies - have peculiar properties (nanoscale size, robust structure, acid resistance, high affinity and specificity, easily produced in bacteria, etc.) that make them ideal choices as LAB-produced immunotherapeutic agents. The present review examines the advantages offered by LAB for the in situ production of therapeutic proteins in the human GIT, discusses the use of in situ-produced VHH antibody fragments, and assesses the usefulness of this strategy in the treatment of infectious and non-infectious gastrointestinal diseases.